Compliant rolling-contact architected materials for shape reconfigurability. Issue 1 (December 2018) - Shaw, Lucas; Chizari, Samira; Dotson, Matthew; Song, Yuanping; Hopkins, Jonathan
Abstract Architected materials can achieve impressive shape-changing capabilities according to how their microarchitecture is engineered. Here we introduce an approach for dramatically advancing such capabilities by utilizing wrapped flexure straps to guide the rolling motions of tightly packed micro-cams that constitute the material's microarchitecture. This approach enables high shape-morphing versatility and extreme ranges of deformation without accruing appreciable increases in strain energy or internal stress. Two-dimensional and three-dimensional macroscale prototypes are demonstrated, and the analytical theory necessary to design the proposed materials is provided and packaged as a software tool. An approach that combines two-photon stereolithography and scanning holographic optical tweezers is demonstrated to enable the fabrication of the proposed materials at their intended microscale. The authors introduce a compliant rolling-contact architected material as a class of shape reconfigurable mechanical metamaterial. They also devise an approach that combines two photon stereolithography and scanning holographic optical tweezers, which allows them to fabricate these architected materials on the microscale.